Keanekaragaman katak dan kodok (Amphibia: Anura) di Suaka Margasatwa Paliyan, Gunungkidul, Yogyakarta - Donan Satria Yudha; Rury Eprilurahman; Hastin Ambar Asti; Herofi Azhar; Nurrochmah Wisudhaningrum; Puji Lestari; Siti Markhamah; Imam Sujadi (Program Studi Biologi, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Udayana, 2019)
Frogs and toads commonly found by human. Frogs and toads could become a bio-indicator of anenvironment. Paliyan Wildlife Sanctuary is a forest area which posses several animal to protect and it’slocated in Gunungkidul Regency, Province of DIY. The diversity of frogs and toads in this wildlifesanctuary is not yet recorded and published. The aim of this research is to understand the diversity of frogsand toads in the area of Paliyan Wildlife Sanctuary. The results there were 9 species of frogs and toads, i.e.,Duttaphrynus melanostictus, Ingerophrynus biporcatus, Fejervarya limnocharis, Kaloula baleata,Occidozyga lima, Occidozyga sumatrana, Microhyla orientalis, Microhyla palmipes and Polypedatesleucomystax. The diversity of frogs and toads in the wildlife sanctuary is moderate according to theShannon-Wiener Index with value: 1,43. Area of Paliyan Wildlife Sanctuary is a suitable habitat for frogsand toads due to its location with dense forest, bushes, rivers, lakes and pools as well as least humanactivities.